Development of Biochemical Practice Guide Website Based on Guided Inquiry on Amilum Identification Materials - Agustinus Ridwan; Masriani Masriani; Rody Putra Sartika; Hairida Hairida; Rini Muharini (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
The COVID-19 pandemic has changed the paradigm of the online learning process, which was originally running offline. As a result, facilities and infrastructure, such as practical guidebooks used to support implementing practical activities, must adapt to online conditions. Website-based technology-assisted practicum guides are the right strategy for online learning. In addition, learning activities on the practicum guide website use a contextual approach, such as the guided inquiry method, to train students to develop their critical and scientific thinking skills. However, the reality on the ground shows that the practicum guide used is not website-based, so it has not been able to support learning during the COVID-19 pandemic, and the learning model used has not used the guided inquiry method. This study aims to develop a guided inquiry-based biochemical practicum guide website on starch identification material and determine the feasibility of the website as well as student and lecturer responses to the developed website. This research is development research using the Borg and Gall model. Their research stages consist of needs analysis, planning, product draft development, initial field trials, revisions, field trials, and revisions. The practicum guide website was validated by 11 experts consisting of 2 language experts and three experts in IT, materials, and guided inquiry learning. They collect feasibility data and student and lecturer responses using indirect communication assisted by questionnaires. The feasibility test results of linguistics, IT, inquiry learning, and material experts obtained percentages of 88.3%, 85.5%, 90.5%, and 91.1%, respectively. All aspects show a very decent category. Student responses at the initial field test stage, main field, and lecturer were 85.7%, 88.3%, and 90%, respectively. All aspects of the feasibility test, student and lecturer responses are in the very feasible category. The results of this study indicate that the guided inquiry-based biochemical practicum guide website on starch identification material is very feasible to use. This practicum guide website is expected to help carry out a biochemistry practicum during the COVID-19 pandemic and improve students' thinking skills